EFEKTIVITAS MODEL PEMBELAJARAN SCRAMBLE TERHADAP KEMAMPUAN BERPIKIR KRITIS MATEMATIS SISWA DI SMP NEGERI 2 PANDAN - Wiwin Manalu; Eva Yanti Siregar (JURNAL MathEdu (Mathematic Education Journal), 2019)
The purpose of this study is to illustrate the effectiveness of the use of the Scramble learning model on the ability of critical student mathematics in eighth grade students in SMP Negeri 2 Pandan. The research was conducted by implementing experiments (one group pretest posttest design) with 34 students as samples and they were taken using a random sampling cluster technique of 204 students. Observations and tests are used in collecting data. Based on a descriptive analysis, it was found: (a) The average use of the Scramble learning model was 3.7 (a very good category) and (b) the average student's critical thinking ability before using the Scramble learning model was 51.23 (category And after using the Scramble learning model is 85.52 (good category). Furthermore, by using a pair of ttest samples and helping SPSS version 22, the results showed a significant value of less than 0.05 (0.000 < 0.05). That is, the learning model of Scramble is effectively used in students ' critical thinking skills in class VIII SMP Negeri 2 Pandan.